2017
DOI: 10.5505/tjtes.2017.01678
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s gangrene: A retrospective analysis of 25 patients

Abstract: BACKGROUND: Fournier's gangrene is a surgical emergency that progresses rapidly and insidiously and results in high morbidity and mortality rates unless it is immediately diagnosed and managed. Here we analyze the outcomes of patients who were followed up and treated for Fournier's gangrene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 18 publications
2
50
4
3
Order By: Relevance
“…[5,10] In contrast, studies from the other clinics reported that the female patients composed 56% and 28.8% of the whole patients. [9,11] In our study, the mean age of the patients was 59 years, and 97% of the patients were male.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…[5,10] In contrast, studies from the other clinics reported that the female patients composed 56% and 28.8% of the whole patients. [9,11] In our study, the mean age of the patients was 59 years, and 97% of the patients were male.…”
Section: Discussionmentioning
confidence: 61%
“…[7] Fournier's gangrene is frequently diagnosed in males, but it may affect both genders in every age groups. [9] The reason for the lower prevalence in female patients can be explained by the simple drainage of the female perineum through the vaginal way. Another reason for the low prevalence in women is that most of the articles were reported by urology clinics, which led to males being overreported.…”
Section: Discussionmentioning
confidence: 99%
“…Fournier's gangrene is known to be a rapid onset disease, but studies have shown that application to the hospital is delayed by an average of one week after initial symptoms have presented. [13] In our study, the median time from symptom onset to hospital application was four (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days. Immediate diagnosis and treatment of FG are known to affect prognosis.…”
Section: Discussionmentioning
confidence: 67%
“…The age of the patients hospitalized in the intensive care unit (ICU) was found to be higher than the patients who did not require ICU admittance (65.33±11.63 years vs. 54.39±11.79 years, respectively; p=0.013). Median FGSI score was 2 (0-14), while the median UFGSI score was 4 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Median FGSI and UFGSI scores were found to be higher in patients accepted to the ICU compared to those who were not (4 vs. 2, p=0.025; and 6 vs. 3, p=0.002, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation